Analysis Effective Financial Management Strategies at The Fashion Show at Polbeng Expo Chapter II - Nurasiah Nurasiah; Wan Junita Raflah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This analyze the implementation of financial management strategies in the Fashion Show event at the Polbeng Business Expo Chapter II organized by the International Business Administration Study Program of Bengkalis State Polytechnic. The study focuses on the implementation of financial planning, budgeting, financial reporting, and financial control to ensure effective and efficient event management. A descriptive qualitative research method was employed, and data were collected through interviews, observation, and documentation. The findings indicate that financial management was implemented systematically through budget planning, allocation of financial resources, recording of income and expenditure transactions, and continuous financial monitoring. The initial budget plan of Rp8,758,000 was revised to Rp7,554,000 based on the actual operational requirements during the event. The event was financially supported by funding from the Expo committee, participant registration fees, and sponsorship contributions, enabling all planned activities to be carried out successfully. Furthermore, the implementation of effective financial management strategies improved budget efficiency, strengthened financial transparency and accountability, minimized operational costs, and supported the achievement of the event objectives. Therefore, it can be concluded that effective financial management plays a significant role in ensuring the successful implementation of event activities through proper planning, efficient budget utilization, accurate financial reporting, and continuous financial control.